An Analysis of the Impact of the Sit-at-home Phenomenon on Small and Medium Enterprises’ Productivity and Sustainability in the South-Eastern Nigeria - Ufomba, Ruth E.; Monyei, Francis E.; Ngwu, Robert O.; Ukpere, Wilfred I.; Kelvin-Iloafu, Lovlyn E.; Onodugo, Ifeoma J; Onodugo, Ifeoma J; Onodugo, Ifeoma J (Journal of Ecohumanism, 2025)
Political agitations appear to alter the modus operandi of business ventures globally as their activities are marred during these periods. Currently, the South-eastern region of Nigeria is witnessing such agitations in the form of a Sit-at-Home order placed by political agitators in the region. This study evaluates the impact of sit-at-home threats or orders on the operations of small and medium businesses (SMEs) within the region. The study adopted a survey research approach and incorporated a sample of business operators and owners of four (4) carefully chosen ventures. For data collection, a standardised questionnaire set with a five-point Likert scale was used. The hypotheses were tested using regression analysis, and the findings indicated that sit-at-home orders significantly and negatively impacted SMEs' capacity to sustain productivity. In addition, it recommended that SMEs must create plans to curb the over-arching consequences of sit-at-home on their operations while maintaining a focus on their growth and economic contribution to society.